How UE will get to know no of antenna supported by ENB?

LTE: Is it possible to share an eNodeB among multiple operators dynamically ?

Which state will have India’s first Eco-friendly bridges for the movement of tigers?

What is the GST Rate for the smartwatch in India?

Which bollywood actor holds the record for playing the role of policeman in most of the movie?

C: Implement a stack using queue?

Find the max sum of a sub array using C?

Who is credited to be the first female President of the Supreme Court in United Kingdom (UK)?

Which country to host the men’s World Boxing Championship in 2021?

How do I take large numbers of input around 100000 digits in length in C/C++?

IF

5 - 4 = 23 8 - 1 = 63 6 - 16 = 32 9 - 9 = 78 3 - 9 = 6

Then

3 - 81 = ?

The answer is "0"

the logic is :

sq(5)-sqrt(4)=23

sq(8)-sqrt(1)=63

and so on ..........

sq(3)-sqrt(81)=0

ans=0; how? 5^2-sqrt4=23; 6^2-sqrt16=32; same 3^2-sqrt9=0..

A*A-SQUARE ROOT(B) 5-4=23 (ie) 25-2 8-1=63 (ie)64-1

like wise all so ans is 3-81=9-9=0

(5)^2 - (2)^(1/2) = 25-2=23 simillarly...... 3-81=(3)^2 - (81)^(1/2)=9-9=0

5² - √4 = 25 - 2 = 23 8² - √1 = 64 - 1 = 63 6² - √16 = 36 - 4 = 32 9² - √9 = 81 - 3 = 78 3² - √9 = 9 - 3 = 6

Therefore: 3² - √81 = 9 - 9 = 0

ans is 0 3-81=0. take a square of 3 & square root of 81.

ans=0 because square of ist no.,sqroot of 2nd no. is equal to given no.

Ans - 0 ( a - b ) = square of a- square root of b so 3 -81= 9-9= 0

hey dear friend i think answer will be (3*3=9)-root of 81=0.... so answer will be zero....

square of first - square root of second=0

If 5 - 4 = 23 8 - 1 = 63 6 -16 = 32 9 - 9 = 78 3 - 9 = 6 then 3 - 81 = ?

If 5-4=23, 6-16=32, 9-9=78, 3-9=6 then 3-61=??

If 5 + 4 => 9 3 + 5 => 9 9 + 1 => 9 1 + 6 => 8 4 + 2 => 8 1 + 7 => 7 5 + 6 => 6 3 + 7 => 3 7 + 0 => 0 Then 8 – 1 => ??